Analisis Kebijakan Publik Dalam Mengatasi Kemiskinan Di Indonesia - Setiawan, Imam; Jamaliah, Jamaliah (Rifa'Institute, 2023)
Poverty is a social problem that is always faced by the Indonesian people. This problem is always associated with the economy through the income earned. Poverty is a serious problem because it will affect everyday life, so it is important to overcome the problem of poverty. The purpose of this research is to find out the process of the Indonesian state in alleviating poverty. The research method used is qualitative with a descriptive approach. The results of this study are to determine the development of poverty from the New Order to the era of President Joko Widodo. This process is carried out through policies that are in accordance with the 1945 Constitution and Pancasila. In implementing policies, always consider the impact in the future. Public policy is also one way for the Government to find out the development of the poverty rate in Indonesia. With this policy, it is hoped that the poverty rate will decrease. This economic problem is also closely related to the educational background of the community. Low education, for example, is one component of poverty. This is also the focus of the government to provide good programs for the progress of Indonesia